Altruism and javanese wisdom as the basic values of the millennial da’i personality: Indigenous counseling perspective - Lur Rochman, Kholil; Basit, Abdul (Jurnal Ilmu Dakwah, 2024)
Purpose - This research explores and interprets the altruistic values embedded in K.H. Sa'dullah Majdi's Sun Ngawiti and Bulughotut Thulab texts, and relates them to the behavioral traits of the millennial generation. Method - This research uses a qualitative methodology. It relies on data interpretation through a literature-based approach to comprehensively analyse the texts. Result  -  The research findings reveal that the texts emphasize core altruistic values, including diligence in learning, self-reflection, virtuous character, and compassion. In Islamic teachings, altruism is aligned with the concept of itsar - prioritizing the needs of others over personal interests. Implication –This study underscores the importance of indigenous knowledge in shaping ethical and culturally responsive counseling approaches. Originality/Value - These values are highly relevant for millennials, especially da'wahists, offering a basic framework for becoming agents of social change who champion justice, equality and moderation. *** Tujuan - Penelitian ini mengeksplorasi dan menafsirkan nilai-nilai altruistik yang terkandung dalam teks Sun Ngawiti dan Bulughotut Thulab karya K.H. Sa'dullah Majdi, serta mengaitkannya dengan ciri-ciri perilaku generasi milenial. Metode - Penelitian ini menggunakan metodologi kualitatif. Penelitian ini mengandalkan interpretasi data melalui pendekatan berbasis literatur untuk menganalisis teks secara komprehensif. Hasil - Temuan penelitian mengungkapkan bahwa teks-teks tersebut menekankan nilai-nilai altruistik inti, termasuk ketekunan dalam belajar, refleksi diri, karakter yang berbudi luhur, dan kasih sayang. Dalam ajaran Islam, altruisme disejajarkan dengan konsep itsar - memprioritaskan kebutuhan orang lain di atas kepentingan pribadi. Implikasi -Studi ini menggarisbawahi pentingnya pengetahuan asli dalam membentuk pendekatan konseling yang etis dan responsif secara budaya. Orisinalitas/Nilai - Nilai-nilai ini sangat relevan bagi generasi milenial, terutama para pendakwah, yang menawarkan kerangka kerja dasar untuk menjadi agen perubahan sosial yang memperjuangkan keadilan, kesetaraan, dan moderasi.